Designing plaster mortar for a high-rise building - Kos, Željko (Array, 2019)
The article rethinks the approach to the development of compositions of plaster mortar as the load on the plaster coating located on the 1st or 24th floor of the building differs significantly. To solve the problem within the framework of existing concepts, principles and regulatory requirements are not possible, as they are applicable to the solutions used in low-rise building. To achieve this goal, it is necessary to develop the scientific basis for the design of plaster mortar. In order to do that, it is necessary to analyze the processes occurring in the plaster coating when it is applied and hardened, the knowledge of the mechanism of the destruction of the "masonry - plaster coating" system, and the calculation and evaluation of stresses. The designated physical and mechanical parameters and the selected plaster mortar compositions should ensure the "work" of the system at the maximum level of such stresses.